공간 빅 데이터 분석을 활용한 연령계층 간 주거이동의 공간적 특성(방향성) 차이 - 이창효(Yi, Changhyo) (국토계획, 2020)
이 연구는 대도시권 가구의 주거이동에 대한 공간적 특성, 그중에서도 주거이동의 방향성에 대한 분석 방법론을 제시하고, 이를 실제 주거이동 가구를 대상으로 적용하여연령계층 간 주거이동 방향성에 차이가 있는지 실증함을 목적으로 한다. 이 연구의 결과는 기존 연구들과 달리, 공간 빅 데이터를구축하여 소규모 공간단위 간 주거이동의 특성에 대한 지식정보를 창출하기 위한 방법론을 제시할 뿐만 아니라, 대도시권에서의주거이동과 관련한 연령계층별 차이를 실증분석함으로써 주택및 주거분야 정책 수립에 추가적으로 활용·참조가 가능한 기초자료를 제공할 수 있을 것이다. The volume, distance, and direction of movement are the main research subjects in the study of the spatial characteristics of the residential relocation. This study focuses on the direction of movement in terms of residential relocation and proposes a methodology for analyzing the direction of residential relocation in small-sized spatial units using the spatial big data. In addition, by applying the proposed methodology, it identifies the directional difference in the residential relocation among the various age groups. The proposed directional analysis methodology is a small-unit weighted linear directional mean (sWLDM). This is an improvement over the linear directional mean (LDM) widely used in the spatial analysis, which was applied to the relocated households in the Seoul metropolitan region. The application results were visualized using the geographical information system and analyzed using the root mean square error (RMSE) and a paired t-test. The analysis results showed the directional difference in the residential relocation according to the temporal change, age group, and region. The directional difference in the residential relocation decreased in the age groups over 40 but increased in the groups under 40 years. Moreover, in the regions within the Seoul metropolitan area, the directional differences among the age groups gradually increased from 2005 to 2015. This study has implications in the construction of the existing official statistical data to be used as the spatial big data. In addition, the new methodology that derives new knowledge information in terms of residential relocation direction was proposed. KCI Citation Count: 4